ANALISIS FAKTOR ERGONOMI YANG BERHUBUNGAN DENGAN KELELAHAN KERJA PADA PERAWAT - Andani, Nur; Ariando Salomon, Glendy; Haslan, Hasliana; Hartati, Sri; Nur Janah, Esti (Ensiklopedia of Journal, 2024)
Nurses bear a fairly high workload in carrying out effective nursing service responsibilities. Work fatigue on nurses is one of the problems in human resource management in hospitals. Based on the initial interview that the author conducted with 10 nurses, 7 nurses stated that they were tired at work, their spines were sore, while the other 3 admitted that they did not experience any disturbances. The purpose of the study was to determine the factors of working period, workload and work shifts related to work fatigue on nurses at Ibnu Sina Hospital Pekanbaru. This research is quantitative with a cross sectional design which was carried out at Ibnu Sina Hospital Pekanbaru. The total population as well as the sample amounted to 120 people. Data analysis was univariate and bivariate using Chi Square Test. The results showed that there was a relationship between workload (p value = 0.017, POR = 2.647), years of service (p value = 0.049, POR = 2.452), work shifts (p value = 0.014, POR = 2.846). In conclusion there is a relationship between workload variables, work period and work shifts on work fatigue in nurses at Ibnu Sina Hospital Pekanbaru. It is suggested that the Ibnu Sina Hospital can be an evaluation material for the Ibnu Sina Hospital, especially in the division of work, work shifts that have an impact on the workload of nurses.Keywords: Workload, Work Fatigue, Nurse